2021
DOI: 10.1002/anie.202110873
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic, Intermolecular C−H Bond Functionalization for the Synthesis of Enantioenriched Amides

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 42 publications
9
66
0
Order By: Relevance
“…Finally, density functional theory (DFT) calculations with a truncated system were carried out to explore the nature of the nitrene insertion into propargylic C­(sp 3 )–H bond using model substrate 1a (Figure , see the SI for computational details). DFT calculations describe the putative iron–nitrenoid active species as a triplet ground state, in line with similar reported iron–nitrenoid species . Calculations indicate that nitrene insertion proceeds through a hydrogen atom transfer (HAT) step (TS1 Δ G ‡ = 14.7 kcal·mol –1 , in the triplet state) to initially form a propargyl radical intermediate, which then undergoes a radical rebound step (TS2 Δ G ‡ = 8.2 kcal·mol –1 , in the triplet state) generating the final propargyl amine product (Figure , and Figure S3 in the SI).…”
supporting
confidence: 81%
“…Finally, density functional theory (DFT) calculations with a truncated system were carried out to explore the nature of the nitrene insertion into propargylic C­(sp 3 )–H bond using model substrate 1a (Figure , see the SI for computational details). DFT calculations describe the putative iron–nitrenoid active species as a triplet ground state, in line with similar reported iron–nitrenoid species . Calculations indicate that nitrene insertion proceeds through a hydrogen atom transfer (HAT) step (TS1 Δ G ‡ = 14.7 kcal·mol –1 , in the triplet state) to initially form a propargyl radical intermediate, which then undergoes a radical rebound step (TS2 Δ G ‡ = 8.2 kcal·mol –1 , in the triplet state) generating the final propargyl amine product (Figure , and Figure S3 in the SI).…”
supporting
confidence: 81%
“…In 2021, Athavale et al reported a P411 variant developed through nine rounds of directed evolution which is capable of nitrene transfer of pivaloxyl-amides. 216 In contrast to the P411 enzymes designed for tosylazide as the substrate, the ratedetermining step (RDS) in this variant is not C-H activation but nitrene formation as shown by KIE studies. These variants extend the substrate scope of the benzylic amines while also increasing the TON compared to that of P411-BPA.…”
Section: T H Imentioning
confidence: 99%
“…Enzymatic C–H bond functionalization is an effective strategy for building and diversifying organic molecules. C–H hydroxylation, an important C–H functionalization reaction, is an attractive pathway for synthesizing hydroxy amino acids, which are widely used as chiral building blocks in the pharmaceutical and fine chemical industries. For example, trans -4-hydroxy- l -proline is the functional intermediate for the synthesis of N -alkylpyrrole and carbapenem antibiotics. , Moreover, a series of hydrophobic hydroxy amino acid natural products from legume seeds exhibit important physiological activities; for example, (2 S ,3 R ,4 S )-hydroxyisoleucine (4-HIL) is a natural nonproteinogenic amino acid derived from fenugreek seeds with potential insulinotropic biological activity …”
Section: Introductionmentioning
confidence: 99%